Quality of life in children with chronic kidney disease (with child and parent assessments) - ALPAY, HARİKA (SPRINGER, 2010)
Herein the results of a multicenter study from the Turkish Pediatric Kidney Transplantation Study Group are reported. The aims of this study were to compare the quality of life (QoL) scores of Turkish children who are dialysis patients (DP), renal transplant recipients (TR), and age-matched healthy controls and to compare child-self and parent-proxy scores. The Turkish versions of the Kinder Lebensqualitat Fragebogen (KINDLA (R)) questionnaires were used as a QoL measure. The study group consisted of 211 children and adolescents with chronic kidney disease (CKD) (139 TR and 72 DP aged between 4-18 years; 13.7 A +/- 3.5 years) from 11 university hospitals, 129 parents of these patients, 232 age-matched healthy children and adolescents (aged between 4-18 years; 13.1 +/- 3.5 years) and 156 of their parents. Patients with CKD had lower scores in all subscales except for physical well-being than those in the control group. TR had higher scores in physical well-being, self-esteem, friends' subscales, and total scores than DP. Child-self scores were lower than parent-proxy scores, especially in CKD, DP, and control groups. Concordance between parent-proxy and child-self reports in the TR, DP, CKD, and control groups was only moderate for the majority of subscales (r = 0.41-0.61). It was concluded that parent-proxy scores on the QoL were not equivalent to child-self scores and that evaluating both children's and parents' perspectives were important. Additionally, psychosocial counseling is crucial not only for patients with CKD but also for their parents.
Keywords: Quality of life; Children; Adolescent; Kidney transplantation; Dialysis; STAGE RENAL-DISEASE; PSYCHOSOCIAL ADJUSTMENT; ADOLESCENTS; TRANSPLANTATION; ESRD; PERFORMANCE; CAREGIVER; DIALYSIS; CANCER; PEDSQL